Acesso aos programas de mobilidade internacional no ensino superior: o caso da UFMG à luz de três experiências internacionais - Rezende, Nicole Antunes (2015)
Due to the dynamic and mobile feature that inequalities take in many different contexts and situations, it is known that even when you are able to reduce inequality in access to higher education institutions, it tends to manifest itself in other areas, as it is possible to imagine that may occur in university internationalization programs. In this context, in the present study it has been studied the access to international mobility programs in the case of UFMG, in the light of three foreign universities in different countries, Germany, Portugal and Spain, in order to identify whether / how / with which intensity the conceptual and management dimension of the drawings mobility programs influence the effective application and implementation of exchange for students at the undergraduate level. Data collection was conducted by means of document analysis and semi-structured interviews. Despite several existing initiatives, it was noticed that the issue of equal access to international mobility programs have not filed centrality on the higher education internationalization policies makers’s agenda, including the case of UFMG. Academic studies on internationalization of higher education are not significantly numerous, especially when we are talking about studies which focused analysis would be Brazilian reality. In this sense, it was intended to contribute theoretical and academically with the discussion on internationalization of higher education focused on the issue of access and, in practical terms help managers of higher education institutions in the formulation of new policies and in new internationalization programs drawings each time more accessible, inclusive and democratic.